1997
DOI: 10.1128/jb.179.14.4538-4544.1997
|View full text |Cite
|
Sign up to set email alerts
|

Iron-regulated excretion of alpha-keto acids by Salmonella typhimurium

Abstract: Excretion of ␣-keto acids by clinical isolates and laboratory strains of Salmonella typhimurium was determined by high-performance liquid chromatography analysis of culture supernatants. The levels of excretion increased markedly with increasing iron stress imposed by the presence of ␣,␣-dipyridyl or conalbumin in the medium. The major product was pyruvic acid, but significant concentrations of ␣-ketoglutaric acid, ␣-ketoisovaleric acid, and ␣-ketoisocaproic acid were also observed. Maximal excretion occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
37
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 35 publications
5
37
0
Order By: Relevance
“…While it was formally possible that the increased pyruvate in the culture media of isc mutants was simply the result of a metabolic imbalance caused by inactive enzymes (i.e., those containing [Fe-S] centers), the data suggested that this was a regulated response. Pyruvate, as well as other ␣-keto acids, has been associated with iron chelation in many bacterial systems, including S. enterica (17,28,32,43). This was consistent with our observation that pyruvate levels in the medium were altered in response to iron concentration and that this response required the Fur protein.…”
Section: Discussionsupporting
confidence: 81%
“…While it was formally possible that the increased pyruvate in the culture media of isc mutants was simply the result of a metabolic imbalance caused by inactive enzymes (i.e., those containing [Fe-S] centers), the data suggested that this was a regulated response. Pyruvate, as well as other ␣-keto acids, has been associated with iron chelation in many bacterial systems, including S. enterica (17,28,32,43). This was consistent with our observation that pyruvate levels in the medium were altered in response to iron concentration and that this response required the Fur protein.…”
Section: Discussionsupporting
confidence: 81%
“…MGF production and utilization by S. typhimurium enb-7 has also been observed under certain conditions of iron deficiency (Reissbrodt et al 1997). It is possible that coastal marine bacteria are capable of producing and utilizing the 3 types of siderophores we tested for.…”
Section: Discussionmentioning
confidence: 97%
“…In bacteria, production and utilization of MGF are induced by low iron concentrations in the medium (Drechsel et al 1993, Reissbrodt et al 1997. However, at least for Phaeodactylum tricornutum, utilization of MGF-bound iron is not influenced by low iron conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated previously, the growth medium for B. burgdorferi is complex and difficult to manipulate. In the initial investigations with micromolar amounts of Desferal and dipyridyl, inhibition of growth was not consistent with that reported in the literature for other bacteria (Kesavalu et al, 1999;Poole et al, 1996;Reissbrodt et al, 1997). However, growth of Sh-2-82 was inhibited in BSK-II medium plus 10 mM dipyridyl.…”
mentioning
confidence: 46%